Cerita Perjalanan Nasi “ dari Sawah ke Meja Makan ” dengan Media Edukasi di Sekolah Dasar - Nurul Setiani; Adelia Dwi Valentin; Suryo Sulistyo; Wakinah Wakinah (Lembaga Pengembangan Kinerja Dosen, 2025)
In community service, elementary school children are invited to understand the process of the rice grain chain and how the rice reaches the dining table. This activity not only teaches elementary school children about the rice supply chain, but is also expected to foster a sense of gratitude and appreciation for the food they eat every day. This activity is carried out using interactive storytelling methods using props, discussions and using interactive games. Evaluation is also carried out informally through observations during discussions and games, and by giving short questions to children about their stages and their respective roles. This learning activity contains values ​​from the SDGs, namely ending hunger (SDGs 2) and sustainable consumption (SDGs 12). The purpose of this service is for elementary school children to know the journey of rice from the rice fields to the dining table by using pictures and telling stories for each group, in addition to elementary school children to work together and need each other..